2007
DOI: 10.2138/am.2007.2486
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of meurigite

Abstract: The crystal structure of meurigite, ideally [K(H 2 O) 2.5 ][Fe 8 3+ (PO 4 ) 6 (OH) 7 (H 2 O) 4 ], monoclinic, C2/c, a = 29.018(5), b = 5.1892(6), c = 19.695(3) Å, β = 106.987(1)°, Z = 4, from the Santa Rita mine, New Mexico, has been solved and refi ned to R 1 = 4.69%, wR 2 = 12.6% using 3325 unique [F o > 4σ(F o )] refl ections collected using a Bruker 6000 SMART CCD diffractometer and synchrotron radiation of wavelength 0.41328 Å. The structure of meurigite is a framework consisting of face-sharing octahedra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Kampf et al (2007) found partially occupied K and O(H 2 O) sites in the channels. The K atoms (K1 and K2) form bonds to O atoms in the surrounding framework as well as to H 2 O molecules (OW3 and OW4) in the channels.…”
Section: Crystallography and Structurementioning
confidence: 96%
See 4 more Smart Citations
“…Kampf et al (2007) found partially occupied K and O(H 2 O) sites in the channels. The K atoms (K1 and K2) form bonds to O atoms in the surrounding framework as well as to H 2 O molecules (OW3 and OW4) in the channels.…”
Section: Crystallography and Structurementioning
confidence: 96%
“…The small peak in the infrared spectrum between 1400 and 1470 cm -1 assignable to CO 2 in meurigite-K is not observed in the meurigite-Na spectrum, indicating little or no CO 2 in meurigite-Na. Water was calculated, based upon the structure of meurigite-K (Kampf et al 2007). The results of four electron microprobe analyses are Wavenumbers (cm -1 ) Absorbance Wavenumbers (cm -1 ) Intensity bending modes, respectively.…”
Section: Infrared and Raman Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations